Scenario-Based Assessment of Indonesia’s Blue Carbon Systems under Restoration and Engineering-Integrated Pathways - Mustofa, Ikrom; Islami, Nur Indah; Darmawan, Ibnu; Azril, Muh; Puspitasari, Rifcha Ayu Dian; Wacano, Dhandhun (Research and Social Study Institute, 2025)
Aims: This study assesses the future potential of Indonesia’s blue carbon ecosystems from an environmental and climate engineering perspective, focusing on mangroves, seagrass beds, and saltmarshes.Methods: Using a desk-based mixed-methods approach, it synthesizes secondary data from global and national sources to compare three development trajectories: Business as Usual, restoration-driven, and engineering-integrated pathways. Rather than relying on spatial modeling or site-specific measurements, the analysis applies an engineering-oriented synthesis that links published ecosystem extent and carbon metrics with documented coastal engineering and restoration cases to infer comparative future carbon performance and resilience.Result: The findings indicate that blue carbon systems can deliver substantially greater and more durable climate benefits when ecological conservation is combined with engineered–nature interventions such as hybrid infrastructure, sediment enhancement, and green coastal buffers. These approaches not only enhance long-term carbon sequestration but also strengthen shoreline protection, biodiversity, and coastal livelihoods. The study identifies persistent gaps in policy integration, financing, and coastal design standards that limit implementation and proposes strategic recommendations for embedding engineering-enhanced blue carbon solutions into Indonesia’s climate policies, including Nationally Determined Contributions, and coastal development planning.Conclusion: Overall, the paper demonstrates the feasibility and relevance of integrating environmental engineering into blue carbon strategies to support climate-resilient coastal development in Indonesia.